2016
DOI: 10.1016/j.bbmt.2016.01.017
|View full text |Cite
|
Sign up to set email alerts
|

The Intravenous Route of Injection Optimizes Engraftment and Survival in the Murine Model of In Utero Hematopoietic Cell Transplantation

Abstract: In utero hematopoietic cell transplantation (IUHCT) has the potential to treat a number of congenital hematologic disorders. Clinical application is limited by low levels of donor engraftment. Techniques that optimize donor cell delivery to the fetal liver (FL), the hematopoietic organ at the time of IUHCT, have the potential to enhance engraftment and the clinical success of IUHCT. We compared the 3 clinically applicable routes of injection (intravenous [i.v.], intraperitoneal [i.p.], and intrahepatic [i.h.])… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 35 publications
(52 reference statements)
3
28
0
Order By: Relevance
“…In particular, 100% of animals receiving intravenous IUT of congenic 10 4 fresh or cultured AFSCs showed stable hematopoietic macrochimerism for up to 6 months, with engraftment in blood and BM exceeding 20%. This remarkable engraftment potential may also be related to the intravenous injection technique which is superior to previously described intraperitoneal delivery and is more applicable to possible clinical translation . This is also demonstrated by our recently published preliminary study in which intraperitoneal IUT of 10 4 congenic AFSCs per fetus resulted in long‐term hematopoietic engraftment only of around 10%, which is approximately half to that achieved in the present study using intravenous IUT .…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…In particular, 100% of animals receiving intravenous IUT of congenic 10 4 fresh or cultured AFSCs showed stable hematopoietic macrochimerism for up to 6 months, with engraftment in blood and BM exceeding 20%. This remarkable engraftment potential may also be related to the intravenous injection technique which is superior to previously described intraperitoneal delivery and is more applicable to possible clinical translation . This is also demonstrated by our recently published preliminary study in which intraperitoneal IUT of 10 4 congenic AFSCs per fetus resulted in long‐term hematopoietic engraftment only of around 10%, which is approximately half to that achieved in the present study using intravenous IUT .…”
Section: Discussionsupporting
confidence: 74%
“…Intravenous IUT was performed at E14 as previously described (see Supporting Information Methods) . Half of the surviving injected offspring in the allogenic group were nursed at birth by naive (noninjected) surrogate mothers in order to exclude transfer of maternal allo‐antibodies through breast milk .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therapeutic intervention in the fetal period may induce immune tolerance and improve efficiency. Finally, prenatal application is feasible via the intraamniotic, vitelline vein, or by fetal intratracheal injection (48)(49)(50)(51). The presence of fetal breathing movements combined with direct contact between the developing airways and amniotic fluid suggests that CRISPR/Cas9 administered via the intraamniotic route could reach the lung epithelium.…”
Section: Crispr As a Therapeutic Strategymentioning
confidence: 99%
“…They were also able to transplant allogeneic skin grafts onto the chimeric mice and observe varying degrees of tolerance towards the grafts. Further studies have shown that the mode of injection [31] is also important for improving engraftment in IUT-HSCs. IUT-HSCs have also been shown to be successful in dogs [32], sheep [33], and monkeys [34, 35].…”
Section: In Utero Stem Cell Transplantation (Table 1)mentioning
confidence: 99%